Season of the Year should be Considered in the Interpretation of Hematology in Carthusian Broodmares - Satué, K.; Gardón, J.C.; Muñoz, A. (Journal of Hematology Research, 2014)
This research was designed to provide data on the influence of the season on the year in the hematology of the Carthusian broodmares. Thirty-eight healthy Carthusian broodmares, aged 7-14 years were sampled during a year every two weeks. Therefore, a total of 24 blood samples were withdrawn for each animal. The following variables were measured: red blood cell count, hemoglobin concentration, packed cell volume, volumetric indexes (mean corpuscular volume, mean corpuscular hemoglobin, mean corpuscular hemoglobin concentration), total white blood cell count and subtypes (neutrophils, lymphocytes, eosinophils, monocytes and basophils), platelet count and serum concentrations. Red blood cell count and packed cell volume were higher in spring. Mean corpuscular volume increased in autumn and mean corpuscular hemoglobin and mean corpuscular hemoglobin concentration decreased in summer and autumn. Platelet count increased in summer. The highest numbers of neutrophils, lymphocytes and eosinophils were found in spring. Serum proteins and neutrophil/lymphocyte ratio remained statistically unchanged during the study. It is concluded that there is seasonality in the hematological parameters of the Carthusian broodmares.